STRATEGI KOMUNIKASI PEMASARAN GAME ONLINE PT. GARENA INDONESIA DALAM MENINGKATKAN JUMLAH KONSUMEN DI KOTA PEKANBARU - Mahyudi, Yusman; ", Rumyeni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Pekanbaru is the strategic areas where the population is increasing and becoming a metropolitan city. Pekanbaru rapid development is also reflected in the rapid growth of existing businesses in various places with an assortment of products. Of course we have a lot of mushrooming cafe-cafe in pekanbaru and this makes the online game publisher also more and more in Indonesia and more genjar conduct marketing strategies such as: Lyto, Gemschool, Megaxus, Mobius, OrangeGame, Prodigy, Garena, and so forth. The presence of publisher-publisher of online games other as competitors serving online gaming service makes PT. Garena Indonesia Pekanbaru should endeavor to increase the number of consumers in addressing the problem of competition between the competitors publisher. The study aims to determine the marketing communication strategy PT. Garena Indonesia Pekanbaru in increasing the number of consumers through sales promotion activities, performed by holding a tournament event, advertising, personal selling, direct marketing.This study uses a qualitative method, namely the collection of data obtained by reality field data through observation, interviews, and documentation. The subjects were seven employees of PT. Garena Indonesia Pekanbaru Branch, 1 Owner cafe, one person loyal consumers, 1 new consumers who have used purposive sampling technique. To analyze the results of this study using interactive data analysis techniques, while the technique of data validity checking through the extension of participation and triangulation.These results indicate that strategy marketing communications PT. Garena Indonesia Pekanbaru in increasing the number of consumers through sales promotion activities on the day their promo and big discount. Advertising activities on television, flyers, banners, banner. Personal selling activities conducting tournament event and the event closed beta test. Activities undertaken in direct marketing using direct mail and telemarketing to consumers while event and sponsorship activities is to hold a tournament event and sponsoring several activities.Keywords: Marketing Communication Strategy, Game Online, Pekanbaru